2022
DOI: 10.1167/jov.22.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity, orientation, and realism increase face uncanniness  by  sensitizing  to  facial distortions

Abstract: The uncanny valley predicts aversive reactions toward near-humanlike entities. Greater uncanniness is elicited by distortions in realistic than unrealistic faces, possibly due to familiarity. Experiment 1 investigated how familiarity and inversion affect uncanniness of facial distortions and the ability to detect differences between the distorted variants of the same face (distortion sensitivity). Familiar or unfamiliar celebrity faces were incrementally distorted and presented either up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 62 publications
(99 reference statements)
6
23
0
Order By: Relevance
“…As sufficient experience with a written language allows holistic processing of words (Björnström et al, 2014; Wong et al, 2010) and sensitivity to configural distortions (Wong et al, 2019), the moderating effect of familiarity on uncanniness can be explained by an intrinsic negative evaluation of stimuli that deviate from learned configural patterns. Familiarity has been shown to moderate the effect of configural deviation on uncanniness in faces (Diel & Lewis, 2022) and novel stimuli (Diel & Lewis, in review). Here, the effect is replicated with text stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As sufficient experience with a written language allows holistic processing of words (Björnström et al, 2014; Wong et al, 2010) and sensitivity to configural distortions (Wong et al, 2019), the moderating effect of familiarity on uncanniness can be explained by an intrinsic negative evaluation of stimuli that deviate from learned configural patterns. Familiarity has been shown to moderate the effect of configural deviation on uncanniness in faces (Diel & Lewis, 2022) and novel stimuli (Diel & Lewis, in review). Here, the effect is replicated with text stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Uncanniness and Deviation From Specialized Categories. Other researchers proposed that heightened sensitivity to deviations in specialized categories, especially faces (Diel & Lewis, 2022;MacDorman et al, 2009a;MacDorman & Chattopadhyay, 2016;Matsuda et al, 2012), amplifies the uncanniness of atypical stimuli. Diel and Lewis (2022) found that participants' sensitivity to uncanniness in deviating faces was increased when faces were familiar compared with novel, and upright compared with inverted, indicating an effect of deviation from familiar stimuli driven by perceptual experience with the stimulus type, driven by an increased ability to detect deviations in specialized categories.…”
Section: Uncanny Valley and Uncanninessmentioning
confidence: 99%
See 3 more Smart Citations